2022
DOI: 10.1038/s41598-022-23842-1
|View full text |Cite
|
Sign up to set email alerts
|

β-caryophyllene and docosahexaenoic acid, isolated or associated, have potential antinociceptive and anti-inflammatory effects in vitro and in vivo

Abstract: Inflammation is a complex biological response involving the immune, autonomic, vascular, and somatosensory systems that occurs through the synthesis of inflammatory mediators and pain induction by the activation of nociceptors. Staphylococcus aureus, the main cause of bacteremia, is one of the most common and potent causes of inflammation in public health, with worse clinical outcomes in hospitals. Antioxidant substances have been evaluated as alternative therapeutic analgesics, antioxidants, anti-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…β-Caryophyllene also exerted anti-inflammatory effects in colitis [ 79 ], skin wound excisions [ 80 ], and sepsis [ 81 ] in animal models. Other in vitro and in vivo approaches highlight the anti-inflammatory action of this sesquiterpene [ 82 , 83 ]. The results suggest that the activity observed in S. aurea could be due to the presence of these compounds, which might act synergistically.…”
Section: Discussionmentioning
confidence: 99%
“…β-Caryophyllene also exerted anti-inflammatory effects in colitis [ 79 ], skin wound excisions [ 80 ], and sepsis [ 81 ] in animal models. Other in vitro and in vivo approaches highlight the anti-inflammatory action of this sesquiterpene [ 82 , 83 ]. The results suggest that the activity observed in S. aurea could be due to the presence of these compounds, which might act synergistically.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that BCP inhibits lipopolysaccharide-induced IL-1β, IL-6, and TNFα production in THP-1 human monocytic cells [ 34 ] and prevents high glucose-induced oxidative stress and inflammation through the inhibition of NF-κB and Nrf2 in mesangial cells [ 35 ]. Moreover, BCP reduces proinflammatory cytokine TNFα, IL-6, and IL-12 production through the inhibition of NLRP3 inflammasome in human peripheral blood mononuclear cells [ 36 ], and alleviated lipopolysaccharide-induced lung inflammation through the inhibition of transforming growth factor β-activated kinase 1 (TAK1)/MAPK-mediated signaling pathways [ 20 ]. These findings suggest that BCP exhibits anti-inflammatory features in various cells and tissues by targeting NF-κB-mediated pathways.…”
Section: Discussionmentioning
confidence: 99%